Analisis Pengembangan Organisasi di Sekolah Dasar Swasta Menggunakan Model Weisbord - Inayati, Yessy; Hamid, Abdul; Samsuddin, Harun (Jurnal Nasional Manajemen Pemasaran dan SDM, 2024)
This study aims to analyze the organizational development at SDIT AbaTaTsa Lahat using the Weisbord Model, which includes six variables: purpose, structure, relationships, rewards, leadership, and work mechanisms. Data were collected through observation, interviews, and documentation, with 10 informants consisting of teachers, staff, students, as well as representatives from the education department and parents. The method used is a qualitative approach with a case study. The results of the study indicate that the overall organizational condition at SDIT AbaTaTsa Lahat is generally good, even approaching excellent, except in the rewards variable. There is a need to improve the rewards for teachers and staff in terms of frequency, amount, and categories to support future organizational development, especially in facing global changes.